Analisis Usability Website Universitas Sumatera Selatan Menggunakan Metode Heuristic Evaluation: Analisis Usability Website Universitas Sumatera Selatan Menggunakan Metode Heuristic Evaluation - Serly Oktarina Serly (Repository STMIK Prabumulih, 2020)
Usability analysis on the University of South Sumatra website helps provide an evaluation in website development. In its approach, this study uses Nielsen's usability theory, where there are five requirements for a website to be usable, namely easy to learn, efficient to use, easy to remember, few errors, and pleasant to use. This study uses a quantitative descriptive approach, with data analysis methods using Heuristic Evaluation techniques. The results of this study are the level of usability of the University of South Sumatra Website, is it easy to learn, efficient, when users interact it is easy to remember procedures/steps without making many mistakes, and finally whether users feel comfortable operating the website. The results of this study can also be used as input innovations for the development of website interfaces and applications that can increase the usability value.